New description of Echiniscus scabrospinosus Fontoura, 1982, and description of a new species of Echiniscus (Heterotardigrada) from China - Pilato, Giovanni; Fontoura, Paulo; Lisi, Oscar; Beasley, Clark (Zootaxa, 2008)
A redescription of Echiniscus scabrospinosus Fontoura, 1982, is presented. A comparison with the more similar species is made, based on information available since the original description. A previously unreported cuticular feature (a central dark ring in the light spots) is described for Echiniscus marginatus Binda & Pilato, 1994. A new species, Echiniscus lineatus sp. nov., is described from China. This new species has a double plate ornamentation with numerous dark polygons and fewer light spots, forming transverse stripes on the plates. Longitudinal stripes are also present on the scapular plate. The new species has lateral filaments A and spines B, C, D, and E, as well as dorsal spines C d and D d .